Effect of storage time and temperature on the physico-chemical and sensory characteristics of coconut tea from dried male (cocos nucifera L.) flowers - Gelido, Eric Miguel L.
The objective of this experiment was to determine the effects of storage time and temperature on the physico-chemical and consumer acceptability of coconut tea produced from dried male Cocos nucifera flowers. Male coconut flowers were dried, roasted, packaged and stored at four temperatures: -18, 37, 42 and 47 °C. After two weeks of storage, all samples exhibited a decrease in moisture and water activity while showing an increase in pH, all attributed to equilibration. The samples were highly alkaline, with pH >8.0. On the other hand, samples experienced a significant decrease in water activity as storage time increased. In terms of color, no changes were observed in the dried tea itself, but a decline in the intensity of the red-orange color was observed in the brewed tea samples, especially in samples stored at 37 and 47°C. Lastly, the moisture of the samples decreased and was found to be significant only for samples stored at 37 and 42 °C. Using the Weibull Accelerated Shelf-life Testing Method, the shelf-life of the tea at 25 °C was calculated to be 17.24 weeks, or four months and 8.23 days, which is near the theoretical value of six months of shelf-life estimated for herbal teas.